Oops! It's Too Late. Your Autonomous Driving System Needs a Faster Middleware - Wu, Tianze; Wu, Baofu; Wang, Sa; Liu, Liangkai; Liu, Shaoshan; Bao, Yungang; Shi, Weisong (IEEE robotics and automation letters, 2021)
Autonomous Driving (AD) has entered a period of rapid development in recent years. With the amount of sensors and control logics installed increasing tremendously to guarantee robustness, a big challenge is posed for AD middleware. Both the academia and the industry are eager for an investigation of the performance of middlewares in Autonomous Driving Vehicles (AVs). To fill this gap, we summarize typical communication scenarios of AVs and evaluate different communication mechanisms of three popular open-source middlewares comprehensively. Besides, we construct a benchmark pack named ComP which consists of a perception communication scenario and a group of real AD applications for researchers to assess middleware performance. Our findings provide useful guidelines for researchers and insightful optimization advice for designing middlewares.